2006
DOI: 10.1016/j.seizure.2006.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic lesion and epilepsy with generalized seizures, ESES and spike-wave paroxysms—Report of three cases

Abstract: We report three patients, who have thalamic lesion and secondary generalized epilepsy with generalized spike wave pattern. The first two patients have unilateral perinatal lesion, one with generalized tonic-clonic seizures on awakening the other with Landau-Kleffner-like syndrome. During the course of the disease both children developed electrical status epilepticus in slow wave sleep (ESES). The third patient has a dominantly unilateral thalamic tumor and epilepsy that mimics juvenile myoclonic epilepsy. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 18 publications
(22 reference statements)
5
45
0
1
Order By: Relevance
“…Only four adult patients with intractable idiopathic generalized epilepsy (IGE) were reported due to unilateral thalamic lesions with generalized SWDs on EEG have been reported. [4] It is known that the thalamus plays a crucial role in the formation of sleep spindles and generalized 3-Hz SWDs. [5] The thalamic reticular nucleus is mostly responsible for forming SWDs and sleep spindles by reciprocal excitatory and inhibitory activities between thalamocortical and nRT neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four adult patients with intractable idiopathic generalized epilepsy (IGE) were reported due to unilateral thalamic lesions with generalized SWDs on EEG have been reported. [4] It is known that the thalamus plays a crucial role in the formation of sleep spindles and generalized 3-Hz SWDs. [5] The thalamic reticular nucleus is mostly responsible for forming SWDs and sleep spindles by reciprocal excitatory and inhibitory activities between thalamocortical and nRT neurons.…”
Section: Discussionmentioning
confidence: 99%
“…[1,3] Thalamus, especially the thalamic reticular nucleus (nRT), was frequently responsible for the formation of generalized spike-wave discharges (SWDs). [4] Involvement of the posterior inferior part of the thalamus is responsible for the generation of SWDs, instead of the medial anterior region, including thalamocortical cells and surrounding reticular nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with shunted hydrocephalus, represented approximately 30% of cases of reported by Veggiotti et al (1999) and by Caraballo et al (2008). Early thalamic lesions seemed to be also strongly associated with sleep-enhanced epileptiform discharges (Monteiro et al, 2001;Kelemen et al, 2006;Guzzetta et al, 2005;Andrade-Machado et al, 2012;Sánchez Fernán-dez et al, 2012;Loddenkemper et al, 2012;Quigg and Noachtar, 2012). Hegyi et al, (2014) in their study of 33 patients with ESES attending the Bethesda Hospital, Budapest, identified sleep EEGs in 171 records, on average 5/patient and wake recordings in 492 records, on average 15/patient).…”
Section: History and Etiology Of Esesmentioning
confidence: 99%
“…В этиологии СПЛ ведущую роль отводят генети-ческим факторам, а также возможности поражения таламуса в перинатальном периоде с нарушением таламо кортикальных связей [12,29,30]. H.Р.…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified